Analog filters using MATLAB - Wanhammar, Lars. (Dordrecht ; London : Springer, 2009)
Analog Filters Using MATLAB provides a comprehensive overview of the theory and modern design methods for frequency-selective analog filters as well as describing how to select and design analog filters using MATLAB. The material covers the synthesis and design of classical passive filters with both lumped and distributed circuit elements, and active filters based on operational amplifiers, transconductors, and current conveyors. A supplementary toolbox in MATLAB is employed in order to minimize the need for advanced mathematics.
Introduction to Analog Filters.- Synthesis of Analog Filters.- Passive Filters.- Filters with Distributed Elements.- Basic Circuit Elements.- First- and Second-Order Sections.- Coupled Forms.- Immitance Simulation.- Wave Active Filters.- Topological Simulation.- Tuning Techniques.
Includes bibliographical references and index.
1
Keywords: MATLAB; Electric filters -- Design and construction